2008
DOI: 10.1590/s1516-31802008000500008
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and asthma among teenagers

Abstract: CONTEXT AND OBJECTIVE: Obesity and asthma are serious and growing problems. Since adipose tissue produces inflammatory substances, the aim of this study was to estimate the prevalence of asthma among students at schools in São José do Rio Preto (Phase 1), and to corroborate the hypothesis for an association between obesity and asthma among these students (Phase 2). DESIGN AND SETTING: Cross-sectional study at Faculdade de Medicina de São José do Rio Preto (Famerp). METHODS: The study consisted of two successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…The association between asthma and obesity could not be established in our study; this is consistent with the data obtained in New Zealand [23], Canada [24] and Brazil [25]; controversially, Jacobson [26] and Garcia-Marcos [27] have found that obesity increased the risk of asthma and that this is more notorious in girls. One possible explanation for this discrepancy arises from the methods employed for evaluating the weight and height of the participants.…”
Section: Discussionsupporting
confidence: 84%
“…The association between asthma and obesity could not be established in our study; this is consistent with the data obtained in New Zealand [23], Canada [24] and Brazil [25]; controversially, Jacobson [26] and Garcia-Marcos [27] have found that obesity increased the risk of asthma and that this is more notorious in girls. One possible explanation for this discrepancy arises from the methods employed for evaluating the weight and height of the participants.…”
Section: Discussionsupporting
confidence: 84%
“…2006). A combined school-age and adolescence population was most frequent, but five studies mainly recruited adolescents (Bertolace et al 2008, Bidad et al 2007, Cassol et al . 2006, Hasan et al .…”
Section: Resultsmentioning
confidence: 99%
“…The developmental stage of the populations recruited in selected studies covered all paediatric age groups from infants (Rodriguez et al 2002), preschoolers (Vargas et al 2007) to adolescents (Gennuso et al 1998, Hasan et al 2006. A combined school-age and adolescence population was most frequent, but five studies mainly recruited adolescents (Cassol et al 2006, Hasan et al 2006, Bidad et al 2007, Bertolace et al 2008, Leung et al 2009). The numbers of subjects analysed in each study varied greatly.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Oliveira et al reviewed the relationships between the walk test, pulmonary function tests and length of hospitalization in cardiac surgery patients 5. Bertolace et al studied the association between obesity and asthma among teenagers 46. Simões et al assessed the prevalence of reduced respiratory muscle strength in institutionalized elderly people 47.…”
Section: Methodsmentioning
confidence: 99%